EFFECT OF HIGH INTENSITY CIRCUIT TRAINING IN PEAK EXPIRATORY FLOW RATE VALUE AMONG MALE YOUNG ADULTS - Yohana Revi Imanita; Endang Ambarwati; Muflihatul Muniroh; Yosef Purwoko (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Lung function has mutual correlation with exercise. Abnormal lung function can affect physical ability to exercise. Otherwise, exercise can increase lung function. Peak expiratory flow rate (PEFR) is a parameter to observe the lung function. High Intensity Circuit Training (HICT) is a combination of aerobic and endurance exercise which has total duration only 7-minutes long. High Intensity Circuit Training can be a good choice for young adults because it does not need much time, easy to be practiced, and beneficial for physical health as well. Objective: To analyze a significant increase in PEFR value after High Intensity Circuit Training for 8 weeks. Methods: This study was a quasi-experimental study with pre-test and post-test comparison group method. Samples were taken purposively from medical student of Diponegoro University (n=56, age=18-21 years old), who were divided into two groups, the control and training group. Peak flow meter was used to measure PEFR value before and after intervention. The data were analysed using Paired T test and Independent T test. Results: A significant increase of PEFR value was found after High Intensity Circuit Training for 8 weeks (p=0.000). The mean difference between pre-test and post-test PEFR value was found increased significantly (p=0.001), that training group had higher score as compared to control group. Conclusion: Regular High Intensity Circuit Training can improve lung function particularly PEFR value in male young adults.